CITRA WAHABI DI MEDIA MASSA - Arina Rahmatika (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
The increasingly expansive Wahabi movement in Indonesian has caused debate in various circles, one of which is Nahdhatul Ulama. To answer Wahabi’s development, Nahdhatul Ulama felt it was necessary to provide a response, one of which was through Aula Magazine on edition February 2016. This research uses a descriptive qualitative approach and using analysis media text in the form of discourse analysis model Van Dijk. The results obtained are imagery of Wahabi portrayed as an organization that is dangerous for Indonesia because the way of dakwah wahabi is straigh, as Wahabi sometimes blamming someone that doing something different with Nabi Muhamamd (bid’ah) and after that bid’ah can become worse like call someone kafir.